OPTIMIZATION OF CONVERGENT-DIVERGENT LAVAL NOZZLE TO PRODUCE NANO PARTICLES - RAJABI, EHSAN ZHALEH (2013)
This research work provides detailed information on numerical modeling of nucleation and condensation based on classical nucleation theory and computational fluid dynamic simulation of heat transfer coefficient of the nozzle wall. The first objective is modeling of condensation of water and mercury vapor in a Laval nozzle, using the liquid drop nucleation theory. Influence of nozzle geometry, pressure and temperature on the average drop size is reported. A MATLAB based computer program was used to calculate the nucleation and condensation of water vapor in the nozzle. The simulation results were validated with the experimental data available in the literature for steam condensation. The model reveals that the average drop size is reduced by increasing the divergent angle of the nozzle.